Strengthening the Twenty-first Century Skills of University Students in Facing ASEAN Economic Community - Mery Berlian; Rian Vebrianto; Alaniyah Syafaren (STAI Hubbulwathan Duri, 2021)
This study aims to determine the strengthening of the 21st Century Skills of UPBJJ Pekanbaru and Pangkal Pinang students in dealing with the ASEAN economic community (MEA). The 21st Century Skills strengthening study was motivated by the low competition in economic politics in Indonesia. The study involved 379 students selected based on study programs at the Pekanbaru Open University and Pangkal Pinang. Data in the form of opinions and statements were collected using a questionnaire in the form of a questionnaire and essay. Data obtained were analyzed qualitatively and quantitatively. The results showed that UPBJJ Pekanbaru and Pangkal Pinang students were qualitatively ready to perform 21st-century skills, including digital era literacy, inventive thinking, memorable communication, high productivity, and spiritual norms and values. Based on quantitative data, there is no significant difference in strengthening the 21st Century Skills of UPBJJ Pekanbaru and Pangkal Pinang students.